2009
DOI: 10.1002/pd.2244
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of cerebral lesions acquired in utero and with a late appearance

Abstract: Although no precise figures are available, many congenital brain lesions arise from intrauterine disruption, frequently due to obstetric complications. The most common entities include intracranial hemorrhage, ischemic lesions, thrombosis of venous vessels and infections. Accurate prenatal diagnosis is possible in many of these cases. However, the findings may be subtle, particularly in the early stage of the disruptive process. Identification of these conditions requires therefore specific expertise, the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Picone et al [79] recently reported a case of periconceptional infection in a HIV-positive pregnant women (<6 weeks' gestation) and appearance of US abnormalities at 36 weeks. These observations probably justify a prolonged US follow-up (until delivery) even if fetal infection is diagnosed early during the pregnancy [80]. …”
Section: Resultsmentioning
confidence: 99%
“…Picone et al [79] recently reported a case of periconceptional infection in a HIV-positive pregnant women (<6 weeks' gestation) and appearance of US abnormalities at 36 weeks. These observations probably justify a prolonged US follow-up (until delivery) even if fetal infection is diagnosed early during the pregnancy [80]. …”
Section: Resultsmentioning
confidence: 99%
“…In some cases, porencephalic cyst can also be related to primitive haemorrhage, especially in patients with COL4A1 mutation [8] . Indeed, as reported in our series, these lesions are diagnosed in the second half of pregnancy, most often in the third trimester, and are not present at the time of routine ultrasound screening [9] .…”
Section: Discussionmentioning
confidence: 55%
“…Doppler ultrasound can confi rm the presence of a turbulent fl ow within this formation (Fig. 7.122 ) (Pilu et al 1997 ;Carletti et al 2009 ). This formation may on occasion become echogenic with no vascular fl ow being found.…”
Section: Vein Of Galen Aneurysmsmentioning
confidence: 98%